2012
DOI: 10.1517/17425247.2012.717926
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in polymeric microspheres for parenteral drug delivery—part 2

Abstract: Novel fabrication methods for microspheres have been recently reported but technical challenges and development risks remain high for scale up from bench to industrial commercialization. While the applications of microspheres for delivery of proteins, genes and vaccines have shown promise for clinical use, the approval of newly functionalized polymers as carriers may still face scrutiny on safety and biocompatibility, which can be key factors in securing the regulatory approval of the product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…28,29 PLGA is a biocompatible and biodegradable polymer, and the parenteral products using this polymer have been already approved by the US Food and Drug Administration for human use. 30 Eudragit RL, which contains positively charged quaternary ammonium groups, was used in combination with PLGA to electrostatically interact with the anionic HA, forming an ionically crosslinked network. Aksungur et al 31 reported that there was no difference in the cytotoxicity of PLGA/Eudragit RL NPs and PLGA NPs after 24 or 48 hours of cell incubation.…”
Section: Results and Discussion Preparation And Physicochemical Charamentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 PLGA is a biocompatible and biodegradable polymer, and the parenteral products using this polymer have been already approved by the US Food and Drug Administration for human use. 30 Eudragit RL, which contains positively charged quaternary ammonium groups, was used in combination with PLGA to electrostatically interact with the anionic HA, forming an ionically crosslinked network. Aksungur et al 31 reported that there was no difference in the cytotoxicity of PLGA/Eudragit RL NPs and PLGA NPs after 24 or 48 hours of cell incubation.…”
Section: Results and Discussion Preparation And Physicochemical Charamentioning
confidence: 99%
“…The concentration of HA in aqueous medium was set to 2.0 mg/mL because the concentration of HA in synovial fluid was reduced from 3.5 to below 2.2 mg/mL in osteoarthritic conditions. 30 Figure 4A displays representative optical micrographs of the filamentous NP/HA aggregates. Immediately upon mixing DiR-loaded NPs with HA under gentle agitation, discontinuous and filamentous aggregates ranging in diameter from 5 to 50 μm were precipitated without additional treatment ( Figure 3A).…”
Section: Hyperspectral Imaging Of Np/ha Aggregatesmentioning
confidence: 99%
“…PHB microspheres are useful for targeting drugs to specific infection sites and for prolonged drug release (Mao ., 2012;Joshi and Patel, 2012). The product of degradation of PHB is 3-hydroxy butyric acid which is normally present in human blood and this is advantageous for PHB to be used in medical field (Siraj ., 2014).…”
Section: Microsphere Preparationmentioning
confidence: 99%
“…Under this condition, the production yield is relatively high at about 75–80% for the formulation of polymer: drug ratio did not affect the yield. The mean particle size of the prepared microspheres was found to be 25.3 ± 5.4 μ m and was suitable for implant delivery (prefer 5–30 μ m) . The drug loading of the formulation was 18.5 ± 2.3%.…”
Section: Resultsmentioning
confidence: 96%